Internet Usage and Its Utilization for Outpatient Treatment among Older Adults in Indonesia: Evidence from the 2020 National Socioeconomic Survey - Mugia Bayu Rahardja; Mardiana Dwi Puspitasari; Indra Murty Surbakti (Althea Medical Journal)
Background: Health insurance is essential for older adults to get healthcare services. Interestingly, only around half of older adults in Indonesia had used the health insurance for outpatient care. Recently, internet usage has increased and is considered a predisposing factor for seeking therapy. This study aimed to explore the internet use among older adults for outpatient therapy.